Pengawasan Terhadap Pengaturan Kepala Badan Otorita Ibu Kota Nusantara dalam Sistem Ketatanegaraan Indonesia - Varentina Lorenza (Media Hukum Indonesia (MHI), 2026)
This study examines using a qualitative approach the oversight of regulations established by the Head of the Nusantara Capital City Authority within the Indonesian constitutional system. The analysis focuses on the regulatory authority held by the Head of the Authority, the oversight mechanisms applicable to the regulations issued, and the implications for the rule of law principle, the hierarchy of legislation, and the system of checks and balances in governance. The research stems from the need to critically examine the status of regulations enacted by the Head of the Nusantara Capital City Authority, given that this authority operates within the realm of government administration and carries legal consequences for state institutional governance. The study employs a normative legal research method with a qualitative approach, utilizing statutory, conceptual, and institutional approaches. Legal materials—comprising primary, secondary, and tertiary sources—were analyzed using a descriptive-analytical method. The findings indicate that regulations established by the Head of the Nusantara Capital City Authority are essentially forms of administrative policy regulations derived from specific delegated authority; however, they remain subject to the principles of legality and legal certainty, as well as oversight within the Indonesian constitutional system. Oversight of these regulations may be exercised through preventive or repressive measures, utilizing administrative or executive mechanisms, or through judicial review based on applicable legal principles